Neutron reflection from counterions at the surface of a soluble surfactant solution - Su, T; Lu, JR; Thomas, R; Penfold, J (1997)
The distribution of counterions at a charged surface has been measured directly using neutron specular reflection with isotopic labeling being used to highlight the scattering from the counterions. The system investigated was the soluble surfactant tetramethylammonium dodecyl sulfate with and without added tetramethylammonium chloride. Depending on the conditions a fraction of ions were found to penetrate the surfactant head-group region. The majority of the counterions observed formed a layer adjacent to the head-group layer which must be part of the diffuse layer. These two layers did not, however, account for all the counterions, and the remainder of die diffuse layer could not be observed with certainty. The reason for this is not understood, although it is probably associated with the roughness of the diffuse layer. Using the measured charge density and surface coverage as parameters, the counterion distribution calculated from the Stem-Gouy-Chapman model of the electrical double layer appears to account quite well for the shape of the distribution, although the effect of the "missing" ions made a detailed quantitative comparison impossible.